Mechanical properties of concrete by using palm oil boiler stone (POBS) as partially fine aggregate replacement material - Lilian, Cheah Mui Yeong (2012)
This study deals with the mechanical properties of concrete by using palm oil boiler stone (POBS) as partially fine aggregates replacement material. The objective of this study is to determine the compressive strength, splitting tensile and flexural strength of concrete containing 15%, 25% & 50% POBS as fine aggregate replacement material and obtain the optimum range value of POBS as fine aggregate replacement material. It involves from the early stage of mix design for Grade 30, casting, curing and lastly, mechanical properties testing carry out to determine the strength given by different mix proportions of POBS. Mechanical properties testing are compressive strength test which tested on cube and cylinder samples, splitting-tensile test on cylinder samples only and flexural beam test where mid-point load method is used. The outcome of the results analyzed the optimum strength of concrete is between the range of 10% to 15% of POBS content. The test results shows improvement in concrete strength. In addition, this study indirectly can save cost of material in concrete, solve the issue of landfill mostly been used up for solid wastage and benefits the construction industry by suggestion another method in improving the quality of concrete.